Hepatitis B virus (HBV) reverse seroconversion (RS) can be prevented even in non‐responders to hepatitis B vaccine after allogeneic stem cell transplantation: long‐term analysis of intervention in RS with vaccine for patients with previous HBV infection. Issue 5 (25th August 2014) - Takahata, M.; Hashino, S.; Onozawa, M.; Shigematsu, A.; Sugita, J.; Fujimoto, K.; Endo, T.; Kondo, T.; Tanaka, J.; Imamura, M.; Teshima, T.
Abstract Background Reactivation of hepatitis B virus (HBV) infection, reverse seroconversion (RS), is a serious complication after allogeneic stem cell transplantation (alloHSCT). We previously conducted a post‐transplant hepatitis B vaccine intervention trial and demonstrated the vaccine efficacy in preventing HBV‐RS. This report is an update of the hepatitis B vaccine study. Methods In this trial, 21 patients were enrolled and received a standard 3‐dose regimen of hepatitis B vaccine after discontinuation of immunosuppressants, whereas 25 transplant recipients with previous HBV infection did not receive the vaccine and served as controls. Results None of the 21 patients in the vaccine group developed HBV‐RS and 12 controls developed HBV‐RS in median follow‐up periods of 60 months (range 13–245). HBV vaccine resulted in a positive value of hepatitis B surface antibody (HBsAb) titer in 9 patients, while HBsAb remained negative in 12 patients. Presence of a high titer of HBsAb before vaccination was associated with conversion into HBsAb positivity after vaccination. Conclusion These results demonstrated the long‐term effects of HBV vaccine for preventing HBV‐RS after alloHSCT. Of note, no HBV‐RS occurred, even in patients who did not achieve conversion into HBsAb positivity after vaccination.